An analysis of the interpretation and application of anti-tax avoidance legislation in the Income Tax Act, 58 of 1962 (as amended) - Denhere, Munyaradzi Blessing (Rhodes University, Faculty of Commerce, Department of Accounting)
Assessed losses provide opportunities to avoid taxation by using various arrangements or transactions. Legislation has been introduced to combat these forms of tax avoidance, in the form of sections 20, 20A, 103(2) and 103(4), and sections 80A to 80L. These sections have also frequently been considered by the courts. The research problem was therefore the analysis of the interaction and effect of the provisions in the Income Tax Act dealing with the use of assessed losses for the purpose of tax avoidance, and the case law interpretation of these provisions. The main goal of the research was to critically analyse the scope and effect of sections 20, 20A, and 103(2) and 102(4), and sections 80A to 80L of the Income Tax Act, dealing with assessed losses, together with the interpretation by the courts. The research was situated within the interpretative paradigm, adopted a qualitative approach, with a doctrinal methodology. As the research was carried out using only publicly available documents, no ethical considerations applied. In addressing the goal of the research, the thesis first discussed the concept of tax avoidance and its consequences. The two main interpretative approaches adopted by the courts, including with regard to tax provisions "“ the strict literal and the purposive approaches "“ were described. The thesis then proceeded to analyse sections 20, 20A, 103(2) and 103(4), and sections 80A to 80L, together with the relevant case law, and in the case of sections 80A to 80L, with the use of a hypothetical example, to illustrate the application of the sections. The conclusion arrived at was that the sections discussed in the thesis are adequate to address the problem of the misuse of assessed losses to avoid tax.
Keywords: South Africa. Income Tax Act, 1962; Income tax Law and legislation -- South Africa; Tax evasion -- South Africa; Tax assessment -- South Africa; Statutes -- South Africa Interpretation and construction